Molding material
By using cellulose fibers and saturated aliphatic polyester and highly polar polyester resins with specific molecular weight distribution in composite materials, the problem of mechanical strength reduction caused by the molding heat history is solved, and high mechanical properties under low temperature melting conditions are achieved .
Patent Information
- Application Number
- CN202410848368.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-29
- Filing Date
- 2024-06-27
- Publication Date
- 2024-12-31
AI Technical Summary
The mechanical strength of existing composite materials decreases during the thermal forming history, especially low-temperature molten resins are prone to thermal decomposition, resulting in a decrease in the mechanical properties of the molded products.
Using molding materials containing cellulose fibers and resins, the resin consists of saturated aliphatic polyester and high polar polyester. The resin has a specific maximum value and area ratio in the GPC molecular weight distribution curve to ensure that the high molecular weight components are Maintain mechanical strength when there is a history of forming heat.
Even in the case of a molding heat history, the Chapricot impact strength and bending elastic modulus of the molding material are excellent, and are suitable for applications such as shells of various containers and office equipment.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a molding material. Background Art
[0002] Conventionally, there are known molding materials containing cellulose fibers, resins, etc. For example, Patent Document 1 discloses a composite material containing paper-derived fibers and a biodegradable resin.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent document 1: Japanese Patent Application Publication No. 2000-006142.
[0006] However, conventional composite materials may have reduced mechanical strength when there is a molding heat history, such as when a molded product or a gate material during molding is melted and pelletized and then molded again. Summary of the invention
[0007] One embodiment of the molding material according to the present invention is:
[0008] A molding material containing cellulose fibers and resin
[0009] The resin comprises a saturated aliphatic polyester and a high polar polyester,
[0010] The resin has a local maximum value 2 when the weight average molecular weight is 100,000 or more in a molecular weight distribution curve based on a GPC method, and has a local maximum value 1 when the weight average molecular weight is less than the local maximum value 2,
[0011] The area value under the maximum value 2 is smaller than the area value under the maximum value 1. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a diagram showing the composition of the raw materials of the molding materials of each Example and each Comparative Example, the molding method, and the evaluation results of the molded products (Table 1).
[0013] Figure 2 This is a diagram showing the composition of the raw materials of the molding materials of each Example and each Comparative Example, the molding method, and the evaluation results of the molded products (Table 2).
[0014] Figure 3 This is a diagram showing the composition of the raw materials of the molding materials of each Example and each Comparative Example, the molding method, and the evaluation results of the molded products (Table 3). DETAILED DESCRIPTION
[0015] Hereinafter, the embodiments of the present invention will be described. The embodiments described below are merely examples of the present invention. The present invention is not limited to the following embodiments, and also includes various modifications implemented within the scope of not changing the gist of the present invention. In addition, all the structures described below are not necessarily the necessary structures of the present invention.
[0016] 1. Molding materials
[0017] The molding material involved in one embodiment of the present invention is a molding material comprising cellulose fibers and a resin, wherein the resin comprises a saturated aliphatic polyester and a high-polarity polyester, and the resin has a maximum value 2 when the weight-average molecular weight is greater than 100,000 in a molecular weight distribution curve based on a GPC method, and has a maximum value 1 when the weight-average molecular weight is less than the maximum value 2, and the area value at the maximum value 2 is smaller than the area value at the maximum value 1.
[0018] If there is a molding heat history such as the molding product or the gate material during molding being melted and pelletized and then molded again, the resin in the molding material will degrade due to thermal decomposition. In particular, low-temperature melting resins that melt at less than 200°C are prone to thermal decomposition.
[0019] Therefore, the present inventors have conducted intensive studies and found that when a resin has a moderate amount of a high molecular weight component, mechanical strengths such as Charpy impact strength and flexural modulus are excellent even in the presence of a molding heat history.
[0020] The molding material can be molded by known molding methods such as injection molding and press working. The molded products made from the molding material are suitable for various containers, sheets, housings of office equipment such as printers, and home appliances as substitutes for polystyrene.
[0021] Hereinafter, various raw materials contained in the molding material will be described.
[0022] 1.1 Cellulose fiber
[0023] The molding material according to the present embodiment includes cellulose fibers. The cellulose fibers function as a filler in a molded product, and contribute to increasing the volume of the molding material and improving physical properties such as strength of the molded product.
[0024] Cellulose fiber comes from plants and is a relatively abundant natural raw material. Therefore, by using cellulose fiber, the environmental load is reduced compared to the use of synthetic fibers. Cellulose fiber also has advantages in terms of raw material supply and cost. In addition, cellulose fiber has the highest theoretical strength among various fibers, which also helps to improve the strength of molded products. As cellulose fiber, in addition to using raw pulp, waste paper, old cloth, etc. can also be defibrated and reused.
[0025] Cellulose fibers are mainly formed of cellulose, but may also contain components other than cellulose. As components other than cellulose, for example, hemicellulose, lignin, etc. may be cited. In addition, cellulose fibers may also be subjected to treatments such as bleaching.
[0026] From the viewpoint of improving the appearance of the molded article surface, the fiber length of the cellulose fibers is preferably less than 500 μm, more preferably less than 50 μm. The fiber length of the cellulose fibers is determined by a method in accordance with ISO 16065-2:2007.
[0027] The content of cellulose fiber is preferably 9% by mass or more relative to the total mass of the molding material, more preferably 18% by mass or more, further preferably 27% by mass or more, further preferably 36% by mass or more, and particularly preferably 45% by mass or more. In addition, the content of cellulose fiber is preferably 90% by mass or less relative to the total mass of the molding material, more preferably 80% by mass or less, and further preferably 70% by mass or less. If the content of cellulose fiber is within the above range, there is a tendency to obtain good mechanical strength even in the presence of a molding heat history.
[0028] 1.2 Resin
[0029] The molding material according to the present embodiment contains a resin, and the resin includes a saturated aliphatic polyester and a highly polar polyester.
[0030] Saturated aliphatic polyester plays the role of a resin matrix, ensuring the impact resistance (toughness) of the molded body. However, it has low miscibility with cellulose fibers, and the two are prone to interfacial peeling. Therefore, by using high-polarity polyester, it functions as a miscible solvent for cellulose fibers and saturated aliphatic polyester, and interfacial peeling can be suppressed.
[0031] The content of the resin is preferably equal to or less than the content of the cellulose fibers described above. In this case, there is a tendency that better mechanical strength can be obtained even when there is a molding heat history.
[0032] 1.2.1 Saturated aliphatic polyester
[0033] Saturated aliphatic polyester has thermoplasticity, and when a molded article is produced from the molding material, it melts and bonds the cellulose fibers to each other. In addition, the saturated aliphatic polyester and the cellulose fibers together bear the physical properties of the molded article. The saturated aliphatic polyester may be a polyester having a linear or branched alkylene group, but is preferably a linear alkyl polyester having a linear alkylene group. Such a linear alkyl polyester has improved toughness due to the linear alkylene group, and mainly has a tendency to improve the impact strength of the molded article.
[0034] The saturated aliphatic polyester preferably contains an alkyl dicarboxylic acid having an alkylene group with 2 to 8 carbon atoms and an alkylene glycol having 2 to 8 carbon atoms as raw material monomers, more preferably contains an alkyl dicarboxylic acid having an alkylene group with 2 to 5 carbon atoms and an alkylene glycol having 3 to 5 carbon atoms, and further preferably contains an alkyl dicarboxylic acid having an alkylene group with 2 to 3 carbon atoms and an alkylene glycol having 3 to 4 carbon atoms. When the saturated aliphatic polyester contains the above raw material monomers, there is a tendency that better mechanical strength can be obtained even in the presence of a molding heat history.
[0035] The saturated aliphatic polyester is preferably obtained by copolymerizing the above two raw material monomers. In addition, the copolymerization can be carried out by a known synthesis method.
[0036] Examples of the alkyl dicarboxylic acid include straight-chain saturated aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid. It is preferred to use one or more of these in the synthesis of the saturated aliphatic polyester.
[0037] As the above-mentioned alkylene glycol, for example, diols such as 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol and 1,8-octanediol can be cited. In the synthesis of saturated aliphatic polyester, it is preferred to use one or more of them. The above-mentioned two raw material monomers are relatively easy to obtain and can be suitable for industrial or commercial use.
[0038] As the saturated aliphatic polyester, it is preferred to include one or more of polybutylene succinate, polybutylene succinate-adipate and polyvinyl adipate. These saturated aliphatic polyesters are biodegradable, so the environmental load of the molded product can be reduced, and there is a tendency to obtain better mechanical strength even in the presence of a molding heat history.
[0039] The content of the saturated aliphatic polyester is preferably 9% by mass or more, more preferably 18% by mass or more, and further preferably 27% by mass or more relative to the total mass of the molding material. In addition, the content of the saturated aliphatic polyester is preferably 50% by mass or less, more preferably 45% by mass or less relative to the total mass of the molding material. If the content of the saturated aliphatic polyester is within the above range, there is a tendency to obtain better mechanical strength even in the presence of molding heat history.
[0040] In addition, the content of the saturated aliphatic polyester is greater than the content of the high polar polyester described later, and the total content of the saturated aliphatic polyester and the high polar polyester is preferably less than the content of the above-mentioned cellulose fiber. In this case, there is a tendency to obtain better mechanical strength even in the presence of a molding heat history.
[0041] Furthermore, when the content of the saturated aliphatic polyester is 100 parts by mass, the content of the high polar polyester described later is preferably 10 parts by mass or more and 70 parts by mass or less (preferably 10 parts by mass or more and 50 parts by mass or less, more preferably 10 parts by mass or more and 30 parts by mass or less), and the content of the cellulose fiber is preferably 110 parts by mass or more and 570 parts by mass or less (preferably 110 parts by mass or more and 300 parts by mass or less, more preferably 110 parts by mass or more and 200 parts by mass or less, and even more preferably 110 parts by mass or more and 150 parts by mass or less). In such a case, there is a tendency that better mechanical strength can be obtained even in the presence of a molding heat history.
[0042] 1.2.2 High polarity polyester
[0043] The high polar polyester improves the compatibility of the cellulose fiber with the saturated aliphatic polyester. As a result, the wettability of the saturated aliphatic polyester to the cellulose fiber is improved, mainly improving the flexural strength of the molded product.
[0044] The high polar polyester preferably has a molecular structure with relatively high polarity, and the number of oxygen atoms is 1 or more relative to the number of carbon atoms being 2 in the repeating structure derived from the raw material monomer. In this case, there is a tendency that better mechanical strength can be obtained even in the presence of a molding heat history. Specifically, the high polar polyester preferably contains raw material monomers such as lactic acid, hydroxybutyric acid, oxysuccinic acid, citric acid, malonic acid, succinic acid, serine, threonine, acrylic acid, methyl acrylate, and vinyl acetate as raw material monomers.
[0045] Specifically, the high polar polyester preferably contains one or more polylactic acid, polyhydroxybutyric acid, polyacrylic acid, polymethyl acrylate, polyvinyl acetate, etc. In addition, the high polar polyester may also be a copolymer having a structure derived from lactic acid or acetic acid in the molecular structure, such as polyvinyl succinate, etc. Among them, the high polar polyester preferably contains one or more of polylactic acid and polyhydroxybutyric acid. Such a compound has biodegradability, can reduce environmental load, and has a tendency to obtain better mechanical strength even in the presence of a molding heat history.
[0046] The content of the high polar polyester is preferably 2% by mass or more, more preferably 5% by mass or more, and further preferably 8% by mass or more, relative to the total mass of the molding material. In addition, the content of the high polar polyester is preferably 70% by mass or less, more preferably 50% by mass or less, further preferably 30% by mass or less, and particularly preferably 20% by mass or less, relative to the total mass of the molding material. When the content of the high polar polyester is within the above range, there is a tendency that better mechanical strength can be obtained even in the presence of a molding heat history.
[0047] 1.2.3 Other resins
[0048] The resin contained in the molding material according to the present embodiment may include resins other than saturated aliphatic polyester and high polar polyester. Examples of such resins include olefin resins such as polyethylene and polypropylene, urethane resins, and acrylic resins.
[0049] 1.2.4 Molecular weight distribution
[0050] The resin contained in the molding material according to the present embodiment has a local maximum 2 when the weight average molecular weight is 100,000 or more in the molecular weight distribution curve based on the GPC method, and has a local maximum 1 when the weight average molecular weight is less than the local maximum 2, and the area value at the local maximum 2 is smaller than the area value at the local maximum 1. In this way, since the resin has a moderate high molecular weight component, the mechanical strength can be maintained even if the resin is thermally decomposed due to the molding heat history.
[0051] The GPC method is a gel permeation chromatography method, which can be measured, for example, by the following steps. A device in which two separation columns (TSKgel SuperHZM-H, manufactured by Tosoh) are connected in series on a GPC device (ACQUITY APC, manufactured by Waters) is used as a measuring device. The measuring sample (molding material) is dissolved in chloroform as an eluent, filtered using a filter with a pore size of 0.45 μm, and the dissolved component is subjected to GPC analysis to obtain a molecular weight distribution curve of the resin. Here, the column temperature is set to 40°C, and an IR detector is used as a detector. In addition, polystyrene (manufactured by Agilent) is used as a standard sample.
[0052] As a peak calculation method, for example, it can be as follows. The chromatogram is used as a linear function, and the position where the slope is 0 when differential is used as the peak top. The chromatogram is used as a linear function, and the position where the slope is 0 when differential is used as the peak boundary. The value obtained by vertically dividing the peak from the peak boundary position is calculated as the area value of each peak. In addition, when the peaks are fully separated, the area value can be processed as a separate peak. In addition, when two overlapping peaks can be fully distinguished, it can be processed as a shoulder peak, and the root of the smaller peak is drawn with a straight line to calculate the area value. In addition, peak separation software can also be used to calculate the area of each peak. However, the consistency rate is set to more than 90%.
[0053] The resin contained in the molding material according to the present embodiment has a maximum value 2 when the weight average molecular weight is 100,000 or more in the molecular weight distribution curve based on the GPC method, but the weight average molecular weight is preferably 110,000 or more, more preferably 120,000 or more, and further preferably 130,000 or more. In addition, it is preferred to have a maximum value 2 when the weight average molecular weight is 500,000 or less, more preferably to have a maximum value 2 when the weight average molecular weight is 400,000 or less, and further preferably to have a maximum value 2 when the weight average molecular weight is 300,000 or less. If the maximum value 2 is within the above range, there is a tendency to obtain better mechanical strength even in the presence of a molding heat history.
[0054] The resin contained in the molding material according to the present embodiment has a local maximum value 1 at a weight average molecular weight less than the local maximum value 2 in the molecular weight distribution curve based on the GPC method, but preferably has a local maximum value 1 when the weight average molecular weight is 150,000 or less, more preferably has a local maximum value 1 when the weight average molecular weight is 120,000 or less, and further preferably has a local maximum value 1 when the weight average molecular weight is 100,000 or less. In addition, it is preferred to have a local maximum value 1 when the weight average molecular weight is 30,000 or more, more preferably has a local maximum value 1 when the weight average molecular weight is 50,000 or more, and particularly preferably has a local maximum value 1 when the weight average molecular weight is 60,000 or more. If the local maximum value 1 is within the above range, there is a tendency that better mechanical strength can be obtained even in the presence of a molding heat history.
[0055] Here, (weight average molecular weight of maximum value 2) / (weight average molecular weight of maximum value 1) is preferably greater than 1.0 and less than 5.0, more preferably greater than 1.1 and less than 4.0, further preferably greater than 1.2 and less than 3.5, and particularly preferably greater than 1.5 and less than 3.0. In this case, there is a tendency that better mechanical strength can be obtained even in the presence of a molding heat history.
[0056] 1.3 Cross-linking agent
[0057] The molding material according to the present embodiment may further contain a crosslinking agent. By containing a crosslinking agent, the molecular weight distribution of the resin can be easily adjusted, and there is a tendency that better mechanical strength can be obtained even when there is a molding heat history.
[0058] As a crosslinking agent, it is preferred to have a reactive group that can crosslink with polyester. More specifically, the crosslinking agent preferably has a reactive group selected from carbodiimide, amine, epoxy, isocyanate, blocked isocyanate, carboxylic anhydride, and carboxylic acid. A crosslinking agent having such a reactive group can preferably react with saturated aliphatic polyester and high polar polyester, making it easy to adjust the molecular weight distribution of the resin, and further has a tendency to obtain better mechanical strength even in the presence of a molding heat history.
[0059] As the cross-linking agent, commercially available products can be used, for example, Metablen P-1901 (manufactured by Mitsubishi Chemical Corporation), Denacol EX-321 (manufactured by Nagase ChemteX Corporation, trimethylolpropane polyglycidyl ether), Denacol EX-211 (manufactured by Nagase ChemteX Corporation, neopentyl glycol diglycidyl ether), Duranate E402-B80B (Asahi Kasei Corporation, isocyanate), Carbodilite HMV-5CA-LC (Nisshinbo Chemical Co., Ltd.), Carbodilite Elastostab H01 (Nisshinbo Chemical Co., Ltd.), Sigma-Aldrich: Product No. 188050 (Merck, poly(ethylene-alt-maleic anhydride)), etc.
[0060] The content of the crosslinking agent is preferably 1% by mass or more relative to the total mass of the molding material, and more preferably 2% by mass or more. In addition, the content of the crosslinking agent is preferably 10% by mass or less relative to the total mass of the molding material, and more preferably 8% by mass or less, and further preferably 6% by mass or less. If the content of the crosslinking agent is within the above range, there is a tendency to obtain better mechanical strength even in the presence of a molding heat history.
[0061] In addition, when the total content of the resin is 100 parts by mass, the content of the crosslinking agent is preferably 3 parts by mass or more and 20 parts by mass or less, more preferably 5 parts by mass or more and 15 parts by mass or less, and particularly preferably 7 parts by mass or more and 13 parts by mass or less. If the content of the crosslinking agent is within the above range, there is a tendency that better mechanical strength can be obtained even in the presence of a molding heat history.
[0062] 1.4 Flame retardants
[0063] The molding material involved in this embodiment may contain a flame retardant. The flame retardant may be a known substance. Examples of the flame retardant include inorganic flame retardants such as antimony compounds, metal hydroxides, nitrogen compounds, and boron compounds; and organic flame retardants such as bromine compounds and phosphorus compounds.
[0064] As the flame retardant, commercially available products may be used, and examples thereof include Rabitle FP-110 (manufactured by Mitsui Chemicals, Inc., a phosphazene-based flame retardant) and Exolit OP1230 (manufactured by Clariant, a phosphate-based flame retardant).
[0065] The content of the flame retardant is preferably 5% by mass or more and 30% by mass or less relative to the total mass of the molding material, more preferably 8% by mass or more and 25% by mass or less, and further preferably 10% by mass or more and 20% by mass or less. If the content of the flame retardant is within the above range, the flame retardancy of the molded product is improved, and there is a tendency to obtain better mechanical strength even in the presence of a molding heat history.
[0066] In addition, when the total content of cellulose fiber, saturated aliphatic polyester and high polar polyester is 100 parts by mass, the content of flame retardant is preferably 1 part by mass or more and 20 parts by mass or less, more preferably 5 parts by mass or more and 20 parts by mass or less, and further preferably 10 parts by mass or more and 20 parts by mass or less. If the content of flame retardant is within the above range, the flame retardancy of the molded product is improved, and there is a tendency that better mechanical strength can be obtained even in the presence of molding heat history.
[0067] 1.5 Other ingredients
[0068] The molding material according to the present embodiment may contain other components such as a colorant, an insect repellent, a mildew proof agent, an antioxidant, an ultraviolet absorber, an aggregation inhibitor, and a mold release agent.
[0069] 2. Manufacturing method of molding material
[0070] The method for producing the molding material will be described. A known method can be applied to the production of the molding material. Specifically, for example, the following method can be applied.
[0071] First, the raw materials are kneaded in a single-shaft kneading machine or a double-shaft kneading machine to form strands, and then granulated to form a pelletized molding material.
[0072] In addition, the following method can also be applied as a method for manufacturing a molding material. First, waste paper and pulp materials are roughly shredded by a shredder device to produce cellulose fibers. Then, cellulose fibers, saturated aliphatic polyesters and high-polarity polyesters, as well as a cross-linking agent as required, are weighed and kneaded. Next, the kneaded raw materials are accumulated in the air to form a sheet-like accumulation. The accumulation contains more air and has a lower density, so it is compressed by a calendering device to remove air to increase the density. Next, after heating in a non-contact manner using a heating furnace, a hot pressing device is used to heat and pressurize.
[0073] In the heating furnace and the hot press device, heating is preferably performed at a temperature higher than the melting temperature of the saturated aliphatic polyester and the high polar polyester by about 20° C. This tends to form a sheet in which each raw material is dispersed with reduced unevenness.
[0074] Next, the sheet is cut into a desired shape by a shredder device to form a granular molding material. The desired shape of the molding material is not particularly limited, and is a roughly cubic shape from 2 mm cube to 5 mm cube. The molding material can be manufactured by the above method. In addition, the manufacturing method of the molding material is not limited to the above method.
[0075] 3. Example
[0076] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0077] 3.1 Production of molding materials and test pieces
[0078] exist Figures 1 to 3 Tables 1 to 3 show the composition of the raw materials of the molding materials of each example and each comparative example, the molding method, and the evaluation results of the molded products. Figures 1 to 3 In the columns of the compositions in (Tables 1 to 3), the unit of the numerical value is parts by mass, and a column without a numerical value means that no numerical value is contained.
[0079] right Figure 1 The records in Tables 1 to 3 are supplemented as follows.
[0080] Saturated aliphatic polyester
[0081] ・Polybutylene succinate (trade name Bio PBS FZ71PB, Mitsubishi Chemical Corporation)
[0082] ・Polybutylene succinate-adipate (trade name Bio PBS FD92PB, Mitsubishi Chemical Corporation)
[0083] High polar polyester
[0084] ・Polylactic acid (trade name Terramac (registered trademark) TE-2000, Unitika Co., Ltd.)
[0085] Cellulose fiber
[0086] ・Product name: Guaiba BEKP, CMPC company.
[0087] Crosslinking agent
[0088] ・Cross-linking agent 1 (Metablen P-1901, manufactured by Mitsubishi Chemical Corporation)
[0089] ・Crosslinking agent 2 (Denacol EX-321, manufactured by Nagase ChemteX Co., Ltd., trimethylolpropane polyglycidyl ether)
[0090] ・Crosslinking agent 3 (Denacol EX-321, manufactured by Nagase ChemteX Co., Ltd., neopentyl glycol diglycidyl ether)
[0091] ・Crosslinking agent 4 (Duranate E402-B80B, Asahi Kasei Corporation, isocyanate)
[0092] ・Crosslinking agent 5 (Carbodilite HMV-5CA-LC, Nisshinbo Chemical Co., Ltd.)
[0093] ・Cross-linking agent 6 (Carbodilite Elastostab H01, Nisshinbo Chemical Co., Ltd.)
[0094] ・Crosslinker 7 (Sigma-Aldrich: Product No. 188050, Merck, poly(ethylene-alt-maleic anhydride))
[0095] Flame retardants
[0096] ・Flame retardant 1 (Rabitle FP-110, manufactured by Mitsui Chemicals Fine Chemicals, Ltd., phosphazene-based flame retardant)
[0097] ・Flame retardant 2 (Exolit OP1230, manufactured by Clariant, a phosphate ester flame retardant)
[0098] according to Figures 1 to 3 The molding materials of the examples and comparative examples were manufactured according to the compositions of (Tables 1 to 3). Specifically, saturated aliphatic polyester, high polar polyester, and cellulose fibers were weighed and put into a Technovel twin-shaft kneading machine KZW15TW-45MG for kneading. The kneading conditions were as follows: the maximum heating temperature was set to 180°C and the extrusion discharge volume was set to 1 kg / hr. Then, after being processed into a strand shape, a pelletizing machine was used to make a molding material in a pelletized state.
[0099] For the molding material obtained above, the weight average molecular weight was measured by the GPC method. Specifically, a device in which two separation columns (TSKgel SuperHZM-H, manufactured by Tosoh) were connected in series on a GPC device (ACQUITY APC, manufactured by Waters) was used as a measuring device. The measurement sample (molding material) was dissolved in chloroform as an eluent, filtered with a filter with a pore size of 0.45 μm, and the dissolved component was subjected to GPC analysis, thereby obtaining a molecular weight distribution curve of the resin. Here, the column temperature was set to 40°C, the detector used an IR detector, and polystyrene (manufactured by Agilent) was used as a standard sample. As a peak calculation method, it was performed as described above.
[0100] The molding materials of each embodiment and each comparative example were used to perform molding by injection molding or press processing. Specifically, in both injection molding and press processing, the heating temperature of the molding materials was set to 200° C. As the injection molding apparatus, THX40-5V of Nissei Plastic Industry Co., Ltd. was used, and as the press processing apparatus, hydraulic press PHKS-40BS of Towa Seiki Co., Ltd. was used.
[0101] Here, in Figures 1 to 3 In the molding history of (Tables 1 to 3), "re-granulation once" means that the material subjected to the above molding process is re-granulated and the molding process is performed again in the same manner as above, and "primary" means that the molding process is performed only once without re-granulation. Figures 1 to 3 In the crosslinking agent adding process of (Tables 1 to 3), "regeneration granulation" means adding when the material after the above molding process is re-granulated, and "primary" means adding only when the raw materials are kneaded. In this way, test pieces in each example and each comparative example were obtained.
[0102] 3.2. Evaluation test
[0103] As an indicator of impact strength, Charpy impact strength is used, and the test method is implemented according to ISO179 (JIS K7111). The shape of the test piece is set to a rectangular plate with a long side of 80 mm ± 2 mm, a short side of 4.0 mm ± 0.2 mm, and a thickness of 10.0 mm ± 0.2 mm. The test device uses an impact tester IT of Toyo Seiki Co., Ltd. In the Charpy impact test, the pendulum weight is set to 4J (WR2.14N / m), the lifting angle is set to 150°, the notch remaining width is set to 8.0mm ± 0.2mm, and the notch angle is set to 45°.
[0104] Bending properties were used as an indicator of bending strength, and the test method was implemented in accordance with ISO178 (JIS K7171). The shape of the test piece was set to a rectangular plate with a long side of 80 mm ± 2 mm, a short side of 10.0 mm ± 0.2 mm, and a thickness of 4.0 mm ± 0.2 mm. The test device used was Instron's 68TM-30, and the test was carried out with a support distance of 64 mm.
[0105] With respect to the obtained test results of each level, the strength of the molded product was judged according to the following criteria.
[0106] Judgment Criteria
[0107] A: Charpy impact strength is 7kJ / m 2 The bending modulus is 4000 MPa or more.
[0108] B: Charpy impact strength is 4 kJ / m 2 and the flexural modulus is 4000 MPa or more (except for the range of A judgment).
[0109] C: Charpy impact strength is 4 kJ / m 2 The bending modulus is 4000 MPa or more (except for the ranges of A and B).
[0110] D: Charpy impact strength is 4 kJ / m 2 The bending modulus is 4000 MPa or less (except for the ranges of B and C).
[0111] E: Cannot be formed.
[0112] 3.3 Evaluation results
[0113] The evaluation results are shown in Figures 1 to 3 (Tables 1 to 3).
[0114] Depend on Figures 1 to 3 From the results shown in (Tables 1 to 3), it can be seen that the molding materials involved in each embodiment can obtain good mechanical strength even in the presence of a molding heat history, wherein the molding materials involved in each embodiment are molding materials comprising cellulose fibers and a resin, the resin comprises a saturated aliphatic polyester and a high-polarity polyester, and the resin has a maximum value 2 when the weight average molecular weight is 100,000 or more in the molecular weight distribution curve based on the GPC method, and has a maximum value 1 when the weight average molecular weight is less than the maximum value 2, and the area value at the maximum value 2 is smaller than the area value at the maximum value 1.
[0115] On the other hand, the molding materials according to the comparative examples that do not satisfy the above-mentioned structure cannot obtain good mechanical strength when there is a molding heat history.
[0116] The following contents are derived from the above-mentioned embodiments.
[0117] One embodiment of the molding material according to the present invention is:
[0118] A molding material containing cellulose fibers and resin
[0119] The resin comprises a saturated aliphatic polyester and a high polar polyester,
[0120] The resin has a local maximum value 2 when the weight average molecular weight is 100,000 or more in a molecular weight distribution curve based on a GPC method, and has a local maximum value 1 when the weight average molecular weight is less than the local maximum value 2,
[0121] The area value under the maximum value 2 is smaller than the area value under the maximum value 1.
[0122] In one embodiment of the above-mentioned molding material,
[0123] The molding material may further contain a cross-linking agent.
[0124] In any one of the above-mentioned molding materials,
[0125] The crosslinking agent may have a reactive group selected from carbodiimide, amine, epoxy, isocyanate, blocked isocyanate, carboxylic anhydride, carboxylic acid.
[0126] In any of the above-mentioned molding materials, the molding material may be:
[0127] The content of the saturated aliphatic polyester is greater than that of the high polar polyester,
[0128] The total content of the saturated aliphatic polyester and the high polar polyester is less than the content of the cellulose fiber.
[0129] In any of the above-mentioned molding materials, the molding material may be:
[0130] When the content of the saturated aliphatic polyester is 100 parts by mass,
[0131] The content of the high polar polyester is 10 parts by mass or more and 70 parts by mass or less,
[0132] The content of the cellulose fibers is 110 parts by mass or more and 570 parts by mass or less.
[0133] In any one of the above-mentioned molding materials,
[0134] The saturated aliphatic polyester may contain, as raw material monomers, an alkyl dicarboxylic acid having an alkylene group with 2 to 8 carbon atoms and an alkylene glycol having an alkylene group with 2 to 8 carbon atoms.
[0135] In any one of the above-mentioned molding materials,
[0136] The saturated aliphatic polyester may include one or more of polybutylene succinate, polybutylene succinate-adipate, and polyvinyl adipate.
[0137] In any one of the above-mentioned molding materials,
[0138] The highly polar polyester may have 1 or more oxygen atoms relative to 2 carbon atoms in a repeating structure derived from a raw material monomer.
[0139] In any one of the above-mentioned molding materials,
[0140] The highly polar polyester may include one or more of polylactic acid and polyhydroxybutyric acid.
[0141] In any one of the above-mentioned molding materials,
[0142] The fiber length of the cellulose fibers may be less than 500 μm.
[0143] In any of the above-mentioned molding materials, it can be
[0144] It also contains flame retardants.
[0145] When the total content of the saturated aliphatic polyester, the high polar polyester, and the cellulose fiber is 100 parts by mass, the content of the flame retardant may be 1 part by mass or more and 20 parts by mass or less.
[0146] The present invention is not limited to the above-mentioned embodiments, and various modifications are possible. For example, the present invention includes a configuration substantially the same as the configuration described in the embodiments, for example, a configuration having the same function, method and result, or a configuration having the same purpose and effect. In addition, the present invention includes a configuration in which a non-essential part of the configuration described in the embodiments is replaced. In addition, the present invention includes a configuration that can have the same effect as the configuration described in the embodiments, or a configuration that can achieve the same purpose. In addition, the present invention includes a configuration in which a known technology is added to the configuration described in the embodiments.
Claims
1. A molding material, characterized in that: It is a molding material containing cellulose fibers and resin. The resin comprises a saturated aliphatic polyester and a high polar polyester, The resin has a local maximum value 2 when the weight average molecular weight is 100,000 or more in a molecular weight distribution curve based on a GPC method, and has a local maximum value 1 when the weight average molecular weight is less than the local maximum value 2, The area value under the maximum value 2 is smaller than the area value under the maximum value 1.
2. The molding material according to claim 1, characterized in that The molding material further includes a cross-linking agent.
3. The molding material according to claim 2, characterized in that The crosslinking agent has a reactive group selected from carbodiimide, amine, epoxy, isocyanate, blocked isocyanate, carboxylic anhydride, carboxylic acid.
4. The molding material according to claim 1 or 2, characterized in that: The content of the saturated aliphatic polyester is greater than that of the high polar polyester, The total content of the saturated aliphatic polyester and the high polar polyester is less than the content of the cellulose fiber.
5. The molding material according to claim 1 or 2, characterized in that: When the content of the saturated aliphatic polyester is 100 parts by mass, The content of the high polar polyester is 10 parts by mass or more and 70 parts by mass or less, The content of the cellulose fibers is 110 parts by mass or more and 570 parts by mass or less.
6. The molding material according to claim 1 or 2, characterized in that: The saturated aliphatic polyester contains, as raw material monomers, an alkyl dicarboxylic acid having an alkylene group with 2 to 8 carbon atoms and an alkylene glycol having an alkylene group with 2 to 8 carbon atoms.
7. The molding material according to claim 1 or 2, characterized in that: The saturated aliphatic polyester includes one or more of polybutylene succinate, polybutylene succinate-adipate and polyvinyl adipate.
8. The molding material according to claim 1 or 2, characterized in that: The highly polar polyester has a repeating structure derived from raw material monomers in which the number of carbon atoms is 2 and the number of oxygen atoms is 1 or more.
9. The molding material according to claim 1 or 2, characterized in that: The high-polarity polyester includes one or more of polylactic acid and polyhydroxybutyric acid.
10. The molding material according to claim 1 or 2, characterized in that: The fiber length of the cellulose fibers is less than 500 μm.
11. The molding material according to claim 1 or 2, characterized in that: It also contains flame retardants. When the total content of the saturated aliphatic polyester, the high polar polyester, and the cellulose fiber is 100 parts by mass, the content of the flame retardant is 1 part by mass or more and 20 parts by mass or less.